2021
DOI: 10.1017/ice.2021.167
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-acquired coronavirus disease 2019 (COVID-19) is less symptomatic than community-acquired disease among healthcare workers

Abstract: Objective: We hypothesized healthcare workers (HCW) with high-risk exposures outside the healthcare system would have less asymptomatic coronavirus 2019 (COVID-19) disease and more symptoms than those without such exposures. Design: A longitudinal point prevalence study during August 17- September 4 2020 and December 2nd - 23rd. Setting: Community based teaching health system Participants: All HCS were invited to participate. Among HCW who acquired COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The majority of the studies were at high risk of bias (n=18/21) ( 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) primarily due to the potential for recall bias (e.g. use of self-report surveys), participation bias (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies were at high risk of bias (n=18/21) ( 16 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ) primarily due to the potential for recall bias (e.g. use of self-report surveys), participation bias (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Further, adjustment for several confounding variables that might impact the likelihood of acquiring SARS-CoV-2 or AEs was lacking. Descriptions of SARS-CoV-2 activity in the community and the predominant variant (where greater activity in the community suggests greater infection risk ( 29 )), vaccination status of HCWs, clinical tasks performed by HCWs, use of respirator fit-testing and checking, type and use of additional PPE, comorbidities expected to exacerbate potential AEs (e.g. smoking and allergies ( 34 )), duration of wear and mitigation strategies used to reduce AE incidence or severity were inconsistently reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The update searches identified 492 citations. Two studies ( 3 , 4 ) on the use of masks and the prevention of SARS-CoV-2 done in a health care setting were added for this update; no new studies done in a community setting were identified through literature searches ( Supplement Tables 1 to 3 ).…”
mentioning
confidence: 99%
“…On the basis of 3 observational studies ( 5–7 ) comparing N95 respirators with surgical masks for prevention of SARS-CoV-2 in health care settings, the strength of evidence was previously assessed as insufficient because of inconsistent effects across studies ( Supplement Table 4 ). One new cross-sectional study done in the United States found no statistically significant differences in risk for SARS-CoV-2 seropositivity between N95 respirator and surgical mask use ( 4 ). The study had methodological limitations, including potential recall bias and a 50% participation rate.…”
mentioning
confidence: 99%